Mathematics in Theology, Theology in Mathematics - Krajewski, Stanisław (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
Mathematicians use theological metaphors when they talk in the kitchen of mathematics. How essential is this talk? Have theological considerations and religious concepts influenced mathematics? Can mathematical models illuminate theology? Some authors have given positive answers to these questions, but they do not seem final. It is unclear how religious views influenced the work of those mathematicians who were also theologians. Religious background of some mathematical concepts could have been inessential. Mathematical models in theology have no predictive value. It is, however, important to continue the recently initiated search for the mutual influences of mathematics and theology. (In addition to the references listed at the end of this paper, one can also consult the volume “Theology in Mathematics?” ed. by Stanisław Krajewski and Kazimierz Trzęsicki, Studies in Logic, Grammar and Rhetoric 44 (57), 2016.)